2009
DOI: 10.1590/s0103-64402009000200014
|View full text |Cite
|
Sign up to set email alerts
|

Measuring parental-caregiver perceptions of child oral health-related quality of life

Abstract: The Parental-Caregiver Perceptions Questionnaire (P-CPQ) is an instrument that assesses a parent's or a caregiver's perceptions regarding the impact of children's oral health status on quality of life. The aim of this study was to evaluate the psychometric properties of the Brazilian version of the P-CPQ. Following translation and cross-cultural adaptation, the P-CPQ was tested on 123 parents and caregivers of children between 11 and 14 years of age with dental caries and malocclusions. The parents/caregivers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 13 publications
(22 reference statements)
8
63
2
4
Order By: Relevance
“…10 This form of application was also used in other studies, and did not affect the psychometric evaluation of the instrument. 25,26 The questionnaire test and retest were performed at an interval of 26 to 30 days between the first and the second application; this is consistent with other studies. [19][20][21] The assessment of internal consistency translation of the legend showing "0 -unable" and "10 -proficient," for which respondents suggested that the word "proficient" should be replaced by "able to recognize" (question 7), "able to diagnose" (question 8), and "willing to get involved in the detection" (question 15).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…10 This form of application was also used in other studies, and did not affect the psychometric evaluation of the instrument. 25,26 The questionnaire test and retest were performed at an interval of 26 to 30 days between the first and the second application; this is consistent with other studies. [19][20][21] The assessment of internal consistency translation of the legend showing "0 -unable" and "10 -proficient," for which respondents suggested that the word "proficient" should be replaced by "able to recognize" (question 7), "able to diagnose" (question 8), and "willing to get involved in the detection" (question 15).…”
Section: Discussionsupporting
confidence: 86%
“…24,25 The form of the application of the instrument (self-application) was the same as that used in the original questionnaire. 10 This form of application was also used in other studies, and did not affect the psychometric evaluation of the instrument.…”
Section: Discussionmentioning
confidence: 99%
“…18 Both instruments were developed in Canada and have been translated and verified for use in the Portuguese language. 19,20 The CPQ 11-14 consists of 16 questions distributed among four subscales: oral symptoms (OS), functional limitations (FL), emotional well-being (EW), and social well-being (SW). Each question has five response options: never 5 0; once or twice 5 1; sometimes 5 2; often 5 3; and every day or almost every day 5 4.…”
Section: Ohrqol Assessment Toolmentioning
confidence: 99%
“…The English questionnaires have also been translated into other languages, including Swedish, and validated with good results [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%